If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(b + -1c) + 2c + -3b = 0 (b * 8 + -1c * 8) + 2c + -3b = 0 (8b + -8c) + 2c + -3b = 0 Reorder the terms: 8b + -3b + -8c + 2c = 0 Combine like terms: 8b + -3b = 5b 5b + -8c + 2c = 0 Combine like terms: -8c + 2c = -6c 5b + -6c = 0 Solving 5b + -6c = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '6c' to each side of the equation. 5b + -6c + 6c = 0 + 6c Combine like terms: -6c + 6c = 0 5b + 0 = 0 + 6c 5b = 0 + 6c Remove the zero: 5b = 6c Divide each side by '5'. b = 1.2c Simplifying b = 1.2c
| 6y-1=2y+4 | | 2b+3=5b+15 | | -20-4.6x=-2.3x+16.8 | | -34-154= | | x^2+x-.4444444=0 | | -54=2x | | -(2n-1)+6(n+3)=-4-(7n-1) | | -1.278+t=-1.042 | | j+4= | | -8=n+4 | | x^2-23x+79=0 | | 2b+16a=1 | | 0=-y^2+28y+98 | | 0=y^2+28y+98 | | a^2+b^2=5 | | -3(4n+2)+2(n-6)=-2(n+1) | | 2y+7x=4x | | 9z+5=7x+6 | | 3(2x-6)+6(x-2)=3(3-5x)+5x-7 | | 4(x-2)-3(x-1)=2(x+6) | | (3x-4)(x^2-6x+6)= | | (x+5)(x+5)=25 | | (11+i)+(3-15i)= | | (x^2+15)(x+30)=3000000 | | 6x(x-1)=7-25x | | (x^2+15)(x+30)=300 | | x^2=5(x+280) | | (-4+3i)-(-1+6i)= | | (2x^3+12)(x^2-15)=117 | | (2x^3+12)(x^2-15)=333 | | -4c(3+5)=32 | | (2x^3+12)(x^2-15)=2103 |